2021
DOI: 10.1007/s00442-021-04957-0
|View full text |Cite
|
Sign up to set email alerts
|

Plant and soil nitrogen in oligotrophic boreal forest habitats with varying moss depths: does exclusion of large grazers matter?

Abstract: The boreal forest consists of drier sunlit and moister-shaded habitats with varying moss abundance. Mosses control vascular plant–soil interactions, yet they all can also be altered by grazers. We determined how 2 decades of reindeer (Rangifer tarandus) exclusion affect feather moss (Pleurozium schreberi) depth, and the accompanying soil N dynamics (total and dissolvable inorganic N, δ15N), plant foliar N, and stable isotopes (δ15N, δ13C) in two contrasting habitats of an oligotrophic Scots pine forest. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…Most of the world's research on grazing prohibition has focused on grassland and forest ecosystems and has concentrated on studies related to plant community composition, primary production, soil properties and carbon cycling (Chen et al, 2012;Chen et al, 2016;Hu et al, 2016;Väisänen et al, 2021). For example, Hu et al (2016) found that grazing prohibition increased vegetation biomass and soil carbon content by synthesizing the results of 51 sites in grasslands in China; Olofsson et al (2006) revealed that herbivore exclusion increased primary production in the long term; Moradi et al (2021) showed that soil physicochemical properties had a significant improvement after livestock exclusion.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the world's research on grazing prohibition has focused on grassland and forest ecosystems and has concentrated on studies related to plant community composition, primary production, soil properties and carbon cycling (Chen et al, 2012;Chen et al, 2016;Hu et al, 2016;Väisänen et al, 2021). For example, Hu et al (2016) found that grazing prohibition increased vegetation biomass and soil carbon content by synthesizing the results of 51 sites in grasslands in China; Olofsson et al (2006) revealed that herbivore exclusion increased primary production in the long term; Moradi et al (2021) showed that soil physicochemical properties had a significant improvement after livestock exclusion.…”
Section: Introductionmentioning
confidence: 99%
“…Short-term exclusion of (reindeer) grazing may alleviate trampling-induced soil compaction and disturbances that are known to reduce microbial activity in forest soils (Ponder andTadros 2002, Tuomi et al 2021) and limit plant fine root growth (Väre et al 1996, Ohtonen and Väre 1998, Morneau and Payette 2000. The organic matter content is higher in the shaded habitats at our study site (Väisänen et al 2021). Therefore, we propose that the alleviation of trampling-induced disturbances by reindeer may rapidly increase microbial biomass, decomposition, fine root growth, and root respiration and, thus, C release in the shaded habitats with more resources (Väisänen et al 2021) and not in the drier sunlit habitats.…”
Section: Short-term Exclusion Of Reindeer Rapidly Increases Ecosystem...mentioning
confidence: 66%
“…The organic matter content is higher in the shaded habitats at our study site (Väisänen et al 2021). Therefore, we propose that the alleviation of trampling-induced disturbances by reindeer may rapidly increase microbial biomass, decomposition, fine root growth, and root respiration and, thus, C release in the shaded habitats with more resources (Väisänen et al 2021) and not in the drier sunlit habitats. In addition, in the shaded habitats, the short-term grazer exclusion increased moss depth that significantly explained the magnitude of ecosystem respiration, similar to earlier studies (Goulden and Crill 1997).…”
Section: Short-term Exclusion Of Reindeer Rapidly Increases Ecosystem...mentioning
confidence: 70%
See 2 more Smart Citations